2020
DOI: 10.1055/s-0040-1710506
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and Thrombosis: A National Inpatient Sample Study

Abstract: Introduction Thrombosis is more common in inflammatory bowel disease (IBD) patients than the general population, but disease-specific correlates of thrombosis remain unclear. Methods We performed a retrospective analysis of discharge data from the National Inpatient Sample between 2009 and 2014, using International Disease Classification codes to identify IBD and non-IBD patients with or without thrombosis. We used NIS-provided discharge-level weights to reflect prevalence estimates. Categoric variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
(43 reference statements)
0
9
0
2
Order By: Relevance
“…Homocysteine also promotes the secretion of pro-inflammatory chemokines, and the differentiation of naïve CD4+ T cells into pro-inflammatory T H 17 cells [46]. Homocysteine levels are correlated with thrombotic events, and interestingly, IBD patients have an increased prevalence of thrombosis compared to those without IBD (5-year prevalence, 7.5% vs. 4.5%, p < 0.001) [47]. Furthermore, the patients are at increased risk of mesenteric ischemia (HR 11.2), and female IBD patients have significantly higher risk of MI (HR 1.6) and stroke (HR 2.1) [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Homocysteine also promotes the secretion of pro-inflammatory chemokines, and the differentiation of naïve CD4+ T cells into pro-inflammatory T H 17 cells [46]. Homocysteine levels are correlated with thrombotic events, and interestingly, IBD patients have an increased prevalence of thrombosis compared to those without IBD (5-year prevalence, 7.5% vs. 4.5%, p < 0.001) [47]. Furthermore, the patients are at increased risk of mesenteric ischemia (HR 11.2), and female IBD patients have significantly higher risk of MI (HR 1.6) and stroke (HR 2.1) [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bargen et al first reported an association between venous thromboembolism and IBD in 1936 [7]. In IBD, the incidence of CVST ranges from 0.5% to 6.7% [5], and it is relatively more common in ulcerative colitis than in Crohn's disease [8]. Up to half of all patients with ulcerative colitis will develop extraintestinal manifestations, typically about 15 years after the initial diagnosis [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Das Risiko für thrombembolische Ereignisse bei erwachsenen Patient*innen mit CED ist deutlich erhöht (8,4fach im Vergleich zur Normalbevölkerung) [670,671] und bei Erwachsenen mit einer 8fach erhöhten Mortalität assoziiert [672]. Neben den allgemeinen Risikofaktoren für thrombembolische Ereignisse sind wichtige CEDspezifische Risikofaktoren die chirurgische Therapie, eine hohe Krankheitsaktivität, das Vorhandensein eines Ports, eine Mangelernährung und eine Dehydration [673]. Bei hospitalisierten Patient*innen sind thrombembolische Ereignisse deutlich häufiger als bei ambulanten Patient*innen, allerdings ist auch das Thromboserisiko der nicht hospitalisierten Patient*innen gegenüber der Referenzpopulation signifikant erhöht [670].…”
Section: Kommentarunclassified